Audit risk and articulation errors from different cash flow disclosures: evidence from China*. Issue 5 (3rd September 2019) - Si, Yi; Fonseka, M. M.; Tian, Gao-liang; Feng, Hua
Abstract: We investigate the effects of articulation errors on audit opinions and fees, and moderating effects of the auditor size and different litigation regimes on the relationships between articulation errors on audit opinions and fees in China. We find that auditors are more likely to issue modified audit opinions (MAOs) and charge higher audit fees from their clients with higher absolute articulation errors, especially for big auditors and in high litigation risk regime. We also find that auditors who do not issue MAOs to clients with abnormal articulation errors receive higher fees than auditors who do issue MAOs.